CircCDYL inhibits the expression of C-MYC to suppress cell growth and migration in bladder cancer - Jiayin Sun; Hui Zhang; Dan Tao; Fei Xie; Feng Liu; Chaohui Gu; Miao Wang; Liang Wang; Guosong Jiang; Zhendi Wang; Xingyuan Xiao (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Circular RNAs (circRNAs) have been revealed to play important roles in modulating gene expression and are involved in several pathological processes. However, a large number of the circRNAs in bladder cancer progression remain undetermined. In this study, the expression level of circCDYL was detected by quantitative real-time PCR in bladder cancer tissues. The circCDYL over-expression plasmid was constructed and transfected into bladder cancer cell lines. The cell migration was detected by using transwell migration assay and wound healing assay, and cell cycles were detected by flow cytometry. The relative protein expression was detected by Western blotting. It was found that circCDYL was low expressed in bladder cancer tissues and cell lines. Functionally, over-expression of circCDYL inhibited cell growth and migration. Importantly, over-expression of circCDYL down-regulated the protein level of C-MYC in both EJ and T24T cells, while the mRNA level of C-MYC was not significantly reduced. Furthermore, over-expression of C-MYC could partly reverse the G0/G1 phase cell cycle arrest induced by circCDYL in bladder cancer cells. Our findings suggest that circCDYL functions as a tumor suppressor in bladder cancer by down-regulating the expression of C-MYC, and this circular RNA might be used as a new target for bladder cancer therapy.